Whole-core depletion calculation using domain decomposed continuous-energy Monte Carlo simulation via McBOX with p-CMFD acceleration and inline feedback. (May 2020) - Jo, YuGwon; Kim, HyeonTae; Kim, Yonghee; Cho, Nam Zin
Graphical abstract: Abstract: This paper presents an approach to the continuous-energy Monte Carlo (MC)-based neutronics-thermal/hydraulics-depletion (N-T/H-D) coupled whole-core calculation. To reduce the memory demand for the detailed depletion calculation, the fission and surface source (FSS) iteration method is applied to the domain decomposed MC criticality calculation. For each iteration (i.e., MC cycle), inline feedback calculations are performed for the stable MC-based coupling calculation, where the partial current-based finite difference (p-CMFD) method is embedded to accelerate the convergence of both the critical boron concentration (CBC) and the neutron source distributions. Then, the subpin-level depletion calculations are performed by the Chebyshev rational approximation method (CRAM). The proposed framework was implemented in the continuous-energy MC code, McBOX, developed at Korea Advanced Institute of Science and Technology (KAIST). The detailed depletion analysis on a typical pressurized water reactor problem shows the improved performance of the proposed framework in terms of memory and computing time.